New IGIP Curriculum for Advanced Training of Engineering University Teachers - A. N. Solovyev; V. M. Prikhodko; L. G. Petrova; E. I. Makarenko (Высшее образование в России)
The discussion of the new Curriculum for pedagogical training of teachers of technical disciplines, prior to its approval by the IGIP Executive Committee in the fall of 2019 is considered. The previous version of this Curriculum was approved in 2013. Over the past period, there have been significant changes in the use of ICT in training, discussed in the proposals of the National IGIP Offices, in the proceedings of the Annual IGIP Conferences, including the International Conference ICL-IGIP held in Tallinn on 23–25 September, 2020. At this Conference, IGIP President Hanno Hortsch in his presentation has published the IGIP curriculum in the form of a table (now we present it in translation into Russian) and reported about his vision of its use. The authors formulate their point of view on the topic basing on the overview of the presentations given at this Conference and relevant articles published in the latest issues of the journal “Higher education in Russia”.